INTERTIDAL BARNACLE COMMUNITY OF KETAPANG AND GILIMANUK PORTS THAT SEPARATED BY THE INDONESIAN THROUGHFLOW OF BALI STRAIT - Sulistiono Sulistiono; Diah Etika Maharatih Setiarina; Romanus Edy Prabowo (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Indonesian Throughflow (ITF) flows from the Pacific Ocean through the western route of Makassar Strait and exit directly to the Indian Ocean through Lombok Strait and Bali Strait or flows eastward through the Banda Sea. Bali Strait separates the Ketapang Ferry Port of Banyuwangi on the Jawa side and Gilimanuk Ferry Port of Bali. Ferries connect Jawa and Bali through those ports as the primary mean of transportation. Ship hull and ballast water of those ships act as a proxy for barnacle distribution in their larval stage from one harbor to another so that it could influence the barnacle community of those two ports. The environmental condition of each seaport defines the barnacle community based on the adaptation ability of barnacle. The purpose of this research was to determine the intertidal barnacle diversity on both Ketapang and Gilimanuk seaports and to compare the barnacle community between Ketapang and Gilimanuk seaports. This study was a survey, and simple random sampling technique was used to collect samples. Sample collection was conducted from July to August 2017, and the sample observation and identification were performed at the Faculty of Agriculture Laboratory at Banyuwangi PGRI University. The diversity indexes including Shannon, Brillouin, Simpson, and Evenness were calculated to determine the level of diversity, and Bray-Curtis similarity coefficient was used to compare the intertidal barnacle community. The result showed the intertidal barnacle diversity of Ketapang and Gilimanuk seaports were low, at the level of 0.89, 0.89, 0.41 and 0.27 at Ketapang Ferry Port and 0.81, 0.80, 0.43, and 0.28 at Gilimanuk Ferry Port based on Shannon, Brillouin, Simpson, and Evenness accordingly. The two ports were having a medium similarity of intertidal barnacle community indicated by the Bray-Curtis similarity coefficient analysis score of 0.58.